Using linked data to calculate summary measures of population health: Health-adjusted life expectancy of people with Diabetes Mellitus - Manuel Douglas G; Schultz Susan E (BMC, 2004)
Abstract Objectives To estimate the health-adjusted life expectancy (HALE) from diabetes mellitus (DM) using a population health survey linked to a population-based DM registry. Methods The 1996/97 Ontario Health Survey (N = 35,517) was linked to the Ontario Diabetes Database (N = 487,576). The Health Utilities Index (HUI3) was used to estimate health-related quality of life. HALE was estimated using an adapted Sullivan method. Results Life expectancy at birth of people with DM was 64.7 and 70.7 years for men and women - 12.8 and 12.2 years less than for men and women without DM. The HUI3 was lower for physician-diagnosed DM compared to self-reported DM (0.799 versus 0.872). HALE at birth was 58.3 and 62.8 years for men and women - 11.9 and 10.7 years less than that of men and women without DM. Conclusions The linked data approach demonstrates that DM is an important cause of disease burden. This approach reduces assumptions when estimating the prevalence and severity of disability from DM compared to methods that rely on self-reported disease status or indirect assessment of disability severity.